Greenhouse gas assessment of Brazilian soybean production and postharvest nitrous oxide emissions from crop residues decomposition - Raucci, Guilherme Silva (2015)
Brazil is one of the world\'s largest producers and exporters of soybeans. The oil and meal obtained from grains are important components of biodiesel and animal feed chains. In recent years, international standards and certifications were developed to promote sustainability in the agricultural supply chain. In this context, greenhouse gases (GHG) emissions in the products life cycle has been the main point of interest to the scientific community and consumers. Few studies have evaluated the GHG emissions in soybean cultivation with specific data for the Brazilian reality. The aim of this study was to evaluate the main sources of GHG in soybean production in the State of Mato Grosso, Brazil. We evaluated 55 farms in the crop years of 2007/08, 2008/09 and 2009/10, accounting for 180,000 hectares of soybean cultivation area and totaling 114 individual situations. The results indicated that the largest source of GHG in the soybean production is the decomposition of crop residues (36%), followed by fuel use (19%), fertilizer application (16%), liming (13%), pesticides (7%), seeds (8%) and electricity consumed at the farms (<1%). The average GHG emissions considering the three crop years were 0.186 kg of CO2eq kg-1 of soybean produced. Based on these results, field experiments were conducted to quantify N2O emissions from the decomposition of soybean crop residues in different climatic regions and harvest periods in Brazil. Our results show that, in field conditions, the contribution of N2O emissions from senesced and desiccated residues that remain on field after soybean harvest are unlikely to represent a significant source of N2O loss above normal background soil emissions. These results were also supported by the laboratory incubation experiment, indicating that the IPCC methodology for estimating N2O emissions from soybean crop residues may provide overestimations for the Brazilian conditions. The results of this study provide relevant and specific information to producers, industry and scientific community regarding the environmental impacts associated with soybean production in Brazil